SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN BALITA SEHAT MENGGUNAKAN PENALARAN FUZZY TSUKAMOTO (STUDI KASUS : PUSKESMAS WONOREJO SAMARINDA) - Ratih Kumala Sari; Hamdani Hamdani (Mulawarman University, 2012)
A healthy toddler is a toddler that responsive around them. To increase the number of healthy baby, health workers develop an activity that selection of healthy toddlers. Computer capability as tool to help people to do task easier and more efficient, especially in process rate and result accuracy that given are expected assessment team can decide in way to choose a healthy toddler. Provision of decision support systems to support the selection of healthy toddlers may allow the assessment team chose healthy toddler according to the criteria. Fuzzy reasoning could be used to resolve problem that ambiguous. Method that used in this final project is the Tsukamoto fuzzy inference system with object model of the problem that solved is the selection of healthy toddlers recommendation at the health center Wonorejo, Samarinda. Knowledge principles are built with production method (IF-THEN). Firestrength reached in every fuzzy rules for each knowledge principles and is composed with average weight. Result of average weight is an output of recommendation level. Results from research show that this decision support system help users to get healthy baby alternatives that can be recommended based criteria.